Implementation of accrual accounting by Malaysian federal government: are the accountants ready? - Ismail, Suhaiza; Siraj, Siti Alawiah; Baharim, Shahril (Emerald Group Publishing Ltd., 2018)
Purpose: The purpose of this paper is to examine factors influencing the readiness of public sector accountants to implement the accrual accounting system in the Malaysian Federal Government. The readiness was measured in terms change commitment and change efficacy. Design/methodology/approach: The study uses a questionnaire survey that comprises three factors (change valence, task knowledge and task availability) in predicting readiness to implement the accrual accounting system. Multiple regressions were performed on a total of 165 usable responses received. Findings: The results reveal that change valence, task knowledge and task availability are significant and positively influence the change efficacy of the Federal Government to implement accrual accounting in Malaysia. However, only change valance is a positively significant factor in influencing change commitment. Originality/value: This study is important as it contributes not only by adding to the scant literature assessing the readiness to implement the accrual accounting system but also by providing useful information on determinants of readiness for accrual accounting implementation in supporting the Malaysian Government’s financial transformation agenda. © 2018, Emerald Publishing Limited.